Addressing Health Misinformation: Promoting Accurate and Reliable Information - Surya Kant Tiwari; Saumya Prakash Srivastava; Bhavna Rani; Soni Chauhan (Archives of Medicine and Health Sciences)
Social media platforms have become valuable tools that can be used to improve professional education, patient care and education, promote health habits, and public health programs. In this article, we will explore the phenomenon of health misinformation, its impact on society, and the steps we can take to address and combat it. We will discuss the impact of health-related misinformation on individuals, policymakers, health-care professionals, educators, journalists, and technology platforms. In particular, we discuss the role of technology platforms in combating the spread of misinformation. In addition, we highlight the importance of promoting information literacy, engaging trusted messengers, strengthening media practices, enhancing technology’s platforms’ role, fostering research efforts, encouraging public–private partnerships, empowering health-care professionals, prioritizing health education, and raising public awareness.